2011
DOI: 10.3998/ark.5550190.0012.717
|View full text |Cite
|
Sign up to set email alerts
|

Bicyclic allyltin derivatives through selective “one pot” hydrostannation - Diels-Alder reaction

Abstract: in recognition of their achievements in organic chemistry and their contributions in the development of the field in our country AbstractIn this paper we report a simple "one pot" procedure to functionalized allyltin derivatives from 1-ethynylcyclohexene. Radical addition of trineophyltin hydride gives quantitatively to (Z,E)-1-(2-trineophylstannylvinyl)cyclohexene, a conjugated dienyl-stannane that, via a [4+2] cycloaddition reaction (Diels-Alder) with activated dienophiles, affords substituted bicyclic unsat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…It has been demonstrated that a great number of Lewis acids have been used to promote Diels-Alder reactions with excellent enantioselectivity [15]. In previous work [11] we studied the synthesis of a variety of functionalized allyltin derivatives in high yields through a "one pot" hydrostannation-Diels-Alder reaction as precursors of analogs of non-steroidal compounds acting as selective receptor modulators in the treatment of pathologies such as obesity, diabetes and inflammatory processes. The regio-and stereochemistry of the proposed structures were defined through a detailed spectroscopic analysis and molecular modeling.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been demonstrated that a great number of Lewis acids have been used to promote Diels-Alder reactions with excellent enantioselectivity [15]. In previous work [11] we studied the synthesis of a variety of functionalized allyltin derivatives in high yields through a "one pot" hydrostannation-Diels-Alder reaction as precursors of analogs of non-steroidal compounds acting as selective receptor modulators in the treatment of pathologies such as obesity, diabetes and inflammatory processes. The regio-and stereochemistry of the proposed structures were defined through a detailed spectroscopic analysis and molecular modeling.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies [11], we obtained 4-trineophylstannylbicyclo [4.4.0]dec-5-en-3-yl cyanide (10) and methyl-2-methyl-4trineophylstannylbicyclo[4.4.0]dec-5-ene-2-carboxilate (11) products as enriched mixtures of the "meta" adducts that were unable to separate from the ortho isomers (10′ and 11′). Now, and for our great satisfaction, dienophile 5 gave only one product 10 in the cycloaddition reaction when catalyst II was employed under methods A and B, and methyl-2methylacrylate ( 6) yielded adduct 11 as the only product with catalyst II under method C conditions, although in low yields in both cases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations